Penguatan Minat Pendidikan Tingkat Lanjut di SD Negeri Giriwetan Melalui Program KKN untuk Meningkatkan Kesadaran Siswa akan Pendidikan Berkelanjutan - Queen Aisyah Annastasya; Yunia Rahma Fatika; Muhammad Raihan Alsyahbana; Adib Zanuar Atmadji; Rohan Bagus Hendryan; Caesar Robih Imadulhaq; Ferdinan Ardiyanto; Chornilia Shilvi Putri Januari; Siti Nor Arifah; Bina Arumbinang Wajdi, S.T., M.T. (STIKes Ibnu Sina Ajibarang, 2025)
The Community Service Program (Kuliah Kerja Nyata / KKN) of Universitas Tidar Group 23 in Giriwetan Village, Grabag District, Magelang Regency, was conducted for one month (July 3–August 3, 2025) with the aim of strengthening students’ interest in pursuing higher education at SD Negeri Giriwetan. This topic is important due to the low motivation of students in rural areas, influenced by economic limitations, lack of information, and insufficient environmental support. The study employed a qualitative method through observation, interviews, and documentation to describe the process and impact of the program. Activities included coloring and creating environmental-themed posters, song creation training using Artificial Intelligence (AI), and developing a “Tree of Hopes” containing students’ aspirations. The results indicate an increase in learning motivation, awareness of the importance of education, and interest in technology. The program proved effective through its creative and participatory approach, despite limitations in time and scope. These findings highlight the importance of sustaining similar structured programs to achieve broader and long-term impacts. Furthermore, the program was not only beneficial for students but also had a positive effect on teachers and the surrounding community. Teachers gained exposure to innovative teaching methods and technology-based learning media that can be adapted in future classes. Parents and community leaders became more aware of the role of family and environment in supporting children’s education. The collaboration between university students and local stakeholders created a sense of collective responsibility in shaping the younger generation. In addition, the integration of Artificial Intelligence as a learning tool sparked curiosity among students and introduced them to the relevance of technology in daily life. Although challenges such as limited facilities and short implementation time persisted, the program successfully demonstrated that creativity and participatory engagement could overcome such barriers.